HUBUNGAN POPULASI NGENGAT PENGGEREK BATANG PADI YANG TERTANGKAP PERANGKAP LAMPU DENGAN INTENSITAS SERANGAN PENGGEREK BATANG PADI DI SEKITARNYA - Evana Nuzulia Pertiwi; Gatot Mudjiono; Rina Rachmawati (Universitas Brawijaya, 2013)
ABSTRACTThe data of pest captured by light trap can be utilized to monitor pest attack in anarea, so it can be determined early when the pest will attack that area. Thisresearch was conducted to determine the relationship of amount stem borer mothswhich captured by light trap with the attack intensity in field. The effectivity oflight trap capture started on 7 pm until 10 pm. The highest population of stemborer moth were on 4 week after planted of plant (WAP) and decreased on thenext week. The highest attack intensity were on 5 WAP (3,33%). The morepopulation of stem borer moth which captured by light trap, the bigger percentageof attack intensity that happened in field with determination coeficiency is 0,789.Correlation coefficient (0.888) indicated a very strong relationship level.Keywords: stem borer, light trap, attack, effectivity, correlation.